IMPLEMENTASI PROGRAM SELASA LITERASI (SERASI) DALAM MENGEMBANGKAN KEMAMPUAN BERPIKIR KRITIS UNTUK MENGUATKAN CIVIC SKILLS MURID (STUDI KASUS DI SMP NEGERI 4 LEMBANG) - Ariska, Aas; Bestari, Prayoga; Mulyadi Nugraha, Dadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the implementation of the Tuesday Literacy (SERASI) program at SMP Negeri 4 Lembang on the development of critical thinking and strengthening of students' civic skills through a qualitative approach with a case study method. Data collection was conducted using interview techniques, observation, and documentation with teachers and students. The results of the study indicate that the SERASI program is implemented through structured stages of independent reading, presentations, discussions, and reflection. These stages have proven effective in training students' abilities to focus on problems, construct logical arguments, and draw conclusions. The development of civic intellectual skills and civic participation skills is achieved in an integrated manner through the practice of analyzing social issues, deliberation, and the courage to voice opinions democratically. Operational obstacles such as academic anxiety and sanction-based pseudo-compliance were still found during the implementation. The findings of this study confirm the strategic function of the SERASI program as a significant contextual learning medium for shaping a culture of literacy while preparing critical, intelligent, and democratic citizens.